“Following a Simplified Scheme”: Project Development and Launch of Production at the Solikamsk Sulphite Pulp Mill - Zykin, Ivan V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2023)
During the years of implementation of the first Soviet five-year plans, great attention was paid to the pulp and paper industry. In the forest industry structure, this component was characterised by a weak level of development. The bet was made on the creation of medium and large pulp and paper industries. In the Urals, where there were large reserves of forest resources and rivers, they built several plants. The largest centre of the pulp and paper industry in the Urals and in the eastern regions of the USSR was formed. The purpose of this article is to study the location, design, and launch of production of the Solikamsk Sulphite Pulp Mill. In the mid-1930s, it was decided to build an enterprise. The project involved innovative technological solutions for the pulp and paper industry. The launch of the plant was postponed several times, the project was altered, and the construction was entrusted from the People’s Commissariat of Forest Industry of the USSR to the People’s Commissariat of Internal Affairs of the USSR. In 1940, the Solikamsk Sulphite Pulp Mill became an independent enterprise, but its construction continued. In March 1941, three months before the outbreak of the Great Patriotic War, the company began the production of pulp. The production was only possible within a simplified scheme due to the absence or malfunction of equipment. The performance of the enterprise was set in insignificant volumes. With the outbreak of war, party-state bodies and economic departments continued the construction of the Solikamsk Sulphite Pulp Mill and providing additional equipment. The company’s development was boosted by the evacuation of several industries, the start of the sulphite waste liquor alcohol plant and the construction of a defense plant nearby. This allowed the plant to develop cooperative ties and master new types of products.